Development and Planning Law - Denyer-Green Barry; Navjit Ubhi (New York Routledge Taylor& Francis Group, 2012)
includes bibliographical references and Index
Keywords: City Planning and redevelopment law -- Great Britain; Regional planning -- Law and Legislation -- Great Britain; Land use -- Law and Legislation -- Great Britain